"Purse-String" Capsular Closure for Decreasing Dislocation Rates in Proximal Femur Replacements. (November 2020) - Novack, Thomas A.; Patel, Jay N.; Hoskins, Tyler; Long, Charles; Mazzei, Christopher; Goyette, David; Wittig, James C.
Abstract : Hip joint dislocation is the most common complication after a proximal femur replacement. As the utilization of proximal femur replacements continues to increase, it becomes imperative for surgeons to find the optimal method to decrease postoperative dislocation and its sequelae. These cases often involve extensive soft-tissue deficits that require reconstruction to provide postoperative strength and stability. Patients report good functional outcomes; however, dislocation remains a concern. Although "described" previously in the literature, the authors illustrate the "purse-string" hip joint capsular closure technique to help other surgeons understand it and apply to their practice as deemed necessary. We also present the senior author's results with using a modified version of the "purse-string" hip joint capsular closure technique.